علاقة الوطنيين المغاربة بتركيا وألمانيا خلال الحرب العالمية الأولى - عياشي, عبد الكريم; عقيب, محمد السعيد (جامعة الوادي - University of Eloued, 2018)
Abstract : This article highlights the relationship between the Maghreb patriots, Turkey and Germany, during World War I. As the presence of many of these men in Istanbul and Berlin before, during and after the war drew attention and suspicion. So, we tried to explain that since we have many signs to value the religious relation we have already described or those which are related to the historical backgrounds which connect the two sides or the political interests. We also supported that with examples of the patriots who emerged remarkably during this stage, whether those who have adopted a political means in this relationship or those who used armed force. By examining all of this, we have reached a set of findings in the conclusion of our article.
مقال
Keywords: الحرب العالمية الأولى، تركيا، المغاربة، المانيا